Educational innovation and teacher training. Latest contributions in research - Arroyo Martínez, Laura (Pulso. Revista de educación, 2023)
Review of the book: Hernán, I. y Anguita, J.E. (coords.) (2023). Innovación educativa y formación docente. Últimas aportaciones en la investigación. Dykinson.